1949
DOI: 10.1016/0002-8703(49)90851-0
|View full text |Cite
|
Sign up to set email alerts
|

The precordial electrocardiogram in incomplete right bundle branch block

Abstract: Grozlp I.-The R and R' waves of Lead \'.I are both small and of nearly the same size. The R' deflection does not exceed 5.0 mm. in height. If an S wave is present it is not over 5.0 mm. in depth (Fig. 7,A). This group contains twenty-eight cases. Grofrp II.-The primar!. and secondary R waves of Lead Vr are separated by a deep S deflection aIwa)s more and usually much more than 5.0 mm. in depth. This group contains twenty-two cases, which have been placed in two subgroups as follows: A. The R and R' waves are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1950
1950
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Of the 120 tracings, 106 were of native Indians and 14 of white or mixed race born at sea level but having lived 15 In none of these cases did we find a tall R in such additional leads although the R/S ratio became gvreater than 1.0 in all the 3 eases. A tracimg of this type is presented in figure 3, with additional leads of the right side.…”
Section: M1aterial and Methodsmentioning
confidence: 77%
“…Of the 120 tracings, 106 were of native Indians and 14 of white or mixed race born at sea level but having lived 15 In none of these cases did we find a tall R in such additional leads although the R/S ratio became gvreater than 1.0 in all the 3 eases. A tracimg of this type is presented in figure 3, with additional leads of the right side.…”
Section: M1aterial and Methodsmentioning
confidence: 77%
“…The necropsy distribution of these cases was 2 in the pulmonary heart disease group, 1 in the coronary heart disease group, 3 in the both group, and 1 in the neither group. Barker and Valencia (1949) have suggested using R in VI greater than 15 mm. to indicate right ventricular hypertrophy in the presence of right bundle-branch block, but using this with our criteria has not proved diagnostic.…”
Section: Resultsmentioning
confidence: 99%
“…P wave abnormalities, consisting primarily of increased amplitude and notching in leads II and/or Vi are common3 , 21,22,29 and were seen in 20 (69 per cent) of our patients. First degree atrioventricular block was seen 8 times (28 per cent) and it, too, has been observed by others.6, [22][23][24][25][26][27][28]30 Atrial fibrillation was observed in 2 patients (6 per cent), both of whom had severe hemodynamic alterations.…”
Section: Patent Ductus Arte7°iosusmentioning
confidence: 87%